History of the origin and development of the institute of operational service of economic sectors, lines of work, fixed objects and territories by criminal police divisions - S. A. Chyzh (Bulletin of Kharkiv National University of Internal Affairs)
The main stages of formation and development of the institute of operative service of branches of economy, lines of work, fixed objects and territories by criminal police divisions are investigated, the regularities of formation of this institute in the activity of operative subdivisions through the coverage of normative regulation of their powers are singled out and analyzed. The main periods of the institute of operational service formation are determined: 1) the Soviet period (1919–1990), the characteristic features of which were the formation of the principle of operational maintenance of economic facilities, which provided for the development of detailed plans of preventive measures, operational and reference cases in accordance with industries (specific facilities), approval of schemes for placing agency sources of information depending on the mode of observation and more; 2) the modern period (1991–2014), which was accompanied by the changes in forms of ownership, the emergence of market relations, the development of new forms of management, changes in the status of the service, which fought against economic offenses, the expansion of power; 3) the latest period (2015 and present), characterized by the transformation of forms of ownership, development of entrepreneurial initiative, rethinking the construction of operational services by criminal police units of the economy, lines of work, fixed facilities and territories and expansion in this regard circles of government entities that provide operational maintenance of relevant facilities in the economy. It is emphasized that each of the considered periods is characterized by a radical change in the system, structure, tasks, functions and competencies of economic security units. The necessity of improving the institute of operative service, revision of its basic concepts, taking into account the specifics of operative service for different subjects of operational and investigative activities is proved.